2016
DOI: 10.1377/hlthaff.2015.0756
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Tobacco Cessation: Big Gaps Remain In Efforts To Get Smokers To Quit

Abstract: Medicaid enrollees are about twice as likely as the general US population to smoke tobacco: 32 percent of people in the program identify themselves as smokers. This article provides the first data about the effectiveness of state Medicaid programs in promoting smoking cessation. Our analysis of Medicaid enrollees’ use of cessation medications found that about 10 percent of current smokers received cessation medications in 2013. Every state Medicaid program covers cessation benefits, but the use of these medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 20 publications
4
79
1
Order By: Relevance
“…Communicating to smokers and health care providers that cessation treatments are covered is also important to ensure that they are aware of and use covered treatments (5,7). A recent study found that only approximately 10% of Medicaid enrollees who smoked received a prescription for a tobacco cessation medication in 2013, with wide variation in use of cessation medications across states (10). Medicaid cessation coverage has the greatest effect when it is available to large numbers of smokers and is widely used (5,7).…”
Section: Discussionmentioning
confidence: 99%
“…Communicating to smokers and health care providers that cessation treatments are covered is also important to ensure that they are aware of and use covered treatments (5,7). A recent study found that only approximately 10% of Medicaid enrollees who smoked received a prescription for a tobacco cessation medication in 2013, with wide variation in use of cessation medications across states (10). Medicaid cessation coverage has the greatest effect when it is available to large numbers of smokers and is widely used (5,7).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare costs from smoking-related chronic diseases place a huge burden on Medicaid, the largest public health insurance programme in the USA 119 120. An estimated 15% of all Medicaid expenditures, or $10 billion annually, are attributable to smoking 119 121.…”
Section: Tobacco Cessation Policiesmentioning
confidence: 99%
“…In 2013, only 10% of Medicaid enrolees who were smokers had received cessation medications, and most states spent significantly less on cessation medications in comparison with the estimated cost to Medicaid from smoking-related diseases 120. Disparities in smoking prevalence and use of state Medicaid cessation resources were greatest among non-expansion Medicaid states (19 states have not adopted the ACA Medicaid expansion) compared with those that expanded Medicaid eligibility 120…”
Section: Tobacco Cessation Policiesmentioning
confidence: 99%
“…Primary care providers have consistently under performed in providing tobacco cessation services despite evidence-based guidelines. 3 As Bailey and colleagues point out, this higher rate of prescriptions does not fully explain their results, particularly since the trend toward higher quit rates occurred even among patients in which no cessation medication was ordered. 2 One possibility is referral to smoking cessation counseling, a variable not captured in this study.…”
mentioning
confidence: 91%